Music and Concentration - Pokeržnik, Helena (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter examines the effects of music on concentration and learning outcomes. Music positively influences attention, reduces stress, and improves reaction time, effects that are particularly evident in activities such as driving. In education, music enhances students' concentration, motivation, and mood, contributing to improved learning performance. Research indicates that music of personal choice boosts concentration and reduces stress, while classical music positively impacts brain development and can increase IQ. However, it is crucial that the music is not too loud, as excessive volume can diminish concentration. The use of ambient music in schools can support learning processes and alleviate stress.